TRENDS AND MECHANISMS OF MODERN FINANCIAL MARKET DEVELOPMENT IN THE EXAMPLE OF WORLD EXPERIENCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In order to provide financial support for the strategy of long-term economic development, the problem of increasing the efficiency of the redistribution of financial resources through the mechanism of the financial market must be solved. This article briefly and systematically reveals the trends in the functioning of the financial market that emerged in the late 19th and early 21st centuries, and substantiates its place and role in investment support for the growth of the real sector of the economy.